The impact of service quality on brand equity in public road transport: a case of Zimbabwe United Passengers Company - Toronga, Batsirai Joseph (Midlands State University, 2015)
The research study was carried out to evaluate The Impact of Service Quality on Brand Equity in Public Road Transport a Case of Zimbabwe United Passengers Company. ZUPCO is undoubtedly facing a tough time and is losing credibility with travelling publics. There is need for ZUPCO to shake of its image of perceived poor management, poor maintenance of fleet and generally being unreliable interms of willingness to help it stakeholders and provide prompt services. It is against this background the research sort to find out the impact of service tangibles on brand awareness, to ascertain the impact of service reliability on brand perceptions and to find out the impact of service assurance on brand loyalty. Literature from different scholars was reviewed and discussed to get an appreciation of the impact of service quality on brand equity in the service industry in general and in public road transport. The study adopted a combination of exploratory and causal research designs. Chi-Square was used to test the statistical significance of the research findings. The research study had a target population of 500 respondents and a sample size of 100 respondents. The sample size was made up of 55 customers (cross border travellers), 40 employees and 5 managers. Stratified random sampling, judgemental sampling and convenience sampling techniques were used to select respondents to participate in the research. Questionnaires and interviews were used as key research instruments to collect data. The study revealed that there are statistically significant positive relationships between the following, service tangibles and brand awareness, service reliability and brand perceptions, service assurance and brand loyalty. It was therefore concluded that there is a statistically significant relationship between service quality and brand equity in public road transport. The research recommended ZUPCO to continuously improve and develop a culture a quality within the organization. Improve its physical facilities appearance and offer a service that is in line with customer preferences and tastes in order to offer a service that travellers’ considers value for money.